Tullock contests may be revenue superior to auctions in a symmetric setting - Matros, Alexander; Possajennikov, Alex (Elsevier, 2016)
We consider a symmetric two-player common-value setting where each player gets a private signal about the object value. We show that for some parameter values the equilibrium revenue can be higher in a Tullock contest than in the standard auctions.